Character's identity between deconstruction and research. Refiguration and rememoration in 'Althénopis' (ENTHYMEMA, 2021)
Althénopis, a hybrid and composite work constructed from an elaborate mixture of genres and narrative codes, is a novel that can be approached, as formal and poetic surrender, to autofiction, of which it shares some decisive characteristics, such as the identity indeterminacy of the narrator and the intent to always go beyond the purely factual and autobiographical data. The essay aims to explore the expressive modes, stylistic strategies and at the same time the symbolic value through which Ramondino's writing ceases to be a mere anamnestic reconstruction of a personal experience to become instead an act of analytical understanding and epistemological reconnaissance, a privileged instrument of deconstruction and search for another version of one's self, within a path of self-recognition and self-identification available by virtue of the double process of refiguration and rememoration implemented through the fictional device.
Keywords: Fabrizia Ramondino; Althénopis; Autofiction; Autobiography; Identity